2011
DOI: 10.4049/jimmunol.1002306
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines IL-32 and IL-17 Have Common Signaling Intermediates despite Differential Dependence on TNF-Receptor 1

Abstract: Cytokines IL-32 and IL-17 are emerging as critical players in the pathophysiology of immune-mediated chronic inflammatory diseases. It has been speculated that the molecular mechanisms governing IL-32– and IL-17–mediated cellular responses are differentially dependent on the TNF pathway. In this study, kinome analysis demonstrated that following stimulation with cytokine IL-32, but not IL-17, there was increased phosphorylation of a peptide target corresponding to TNF-R1. Consistent with this observation, bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Although the exact mechanism of this effect need to be further investigated, we believe that miR-26b is intimately involved in RA progression and miR-26b based strategies have the potential to be highly effective against synovium inflammation in RA, consistent with earlier observations by Turner-Brannen et al [50]. Our study is also supported by Tomoyuki Nakasa et al, who presented convincing results that NF-κB activity is critical for the initiation and maintenance of chronic inflammation in RA synovial tissue [15].…”
Section: Resultssupporting
confidence: 88%
“…Although the exact mechanism of this effect need to be further investigated, we believe that miR-26b is intimately involved in RA progression and miR-26b based strategies have the potential to be highly effective against synovium inflammation in RA, consistent with earlier observations by Turner-Brannen et al [50]. Our study is also supported by Tomoyuki Nakasa et al, who presented convincing results that NF-κB activity is critical for the initiation and maintenance of chronic inflammation in RA synovial tissue [15].…”
Section: Resultssupporting
confidence: 88%
“…With this discovery, we investigated the functional role of IL-32θ in the immune response. Despite the conflicting data pertaining to the role of IL-32 in regulating the inflammatory response [2][3][4][5], this study revealed that IL-32θ can regulate CCL5 expression in human myelomonocytic THP-1 cells. Although many reports have emphasized the importance of CCL5 in the development of disease [58,61,62,65], few studies have investigated the mechanisms mediating the effects of IL-32 on CCL5 expression.…”
Section: Discussionmentioning
confidence: 77%
“…The function of interleukin (IL)-32, formerly named natural killer cell transcript 4 [1], has been previously described in several studies [2][3][4][5][6][7]. The protein sequence of IL-32 is distinct in that it is not homologous with any other cytokines [8].…”
Section: Introductionmentioning
confidence: 99%
“…The cells were rested for twenty-four hours, then exposed to the amphiphiles of interest for twenty-four hours. Cell free TC supernatants were monitored for the production of chemokines Groα and IL-8 by ELISA as previously described [31], [34]. The constitutive background level of chemokine Groα was 6.6±1.8 pg/ml, and that of IL-8 was 1.7±0.16 ng/ml.…”
Section: Resultsmentioning
confidence: 99%